Vote Buying and the Quest for Sustainable Democracy: The Nigerian Context - Shehu, Lukman Omomeji; Araba, Akeem Ayanda; Abdulrahman, Ibrahim (Kashere Journal of Politics and International Relations, 2025)
The practice of vote buying poses a significant threat to the sustainability of democracy, particularly in contexts such as Nigeria, where it undermines the principles of free, fair, and credible elections. This study critically examines the phenomenon of vote buying, tracing its historical roots, manifestations, and implications for democratic governance. Drawing on the clientelism theory, the research explores the socio-economic, cultural, and institutional drivers that perpetuate this electoral malpractice. It highlights the transactional nature of vote buying, where financial and material inducements overshadow issue-based political engagement, thereby distorting voter preferences and eroding electoral integrity. The study reveals that vote buying fosters corruption, marginalizes competent leadership, weakens political accountability, and exacerbates electoral violence. Furthermore, it perpetuates a culture of impunity, undermining public trust in democratic institutions and processes. To address these challenges, the study recommends comprehensive poverty alleviation strategies, robust enforcement of electoral laws, and intensified voter education campaigns. It also emphasizes the need for institutional reforms to enhance the transparency and credibility of the electoral process. By addressing the root causes of vote buying, this study advocates for a more inclusive and democratic system that reflects the genuine will of the people.